Enhancing Restaurant Business Growth in Indonesia: a Maslahah Perspective on Culinary Industry Development - Wulandari, Suci; Jannah, Nurul; Harahap, M. Ikhsan (Tasharruf: Journal Economics and Business of Islam, 2026)
This research investigates the challenges in business growth faced by Rumah Makan Rani in Laugendek, Berastagi, especially the drop in customer numbers due to limited menu innovation and weak online promotion. The goal is to analyze both internal and external factors contributing to this decline, focusing on operational and customer-related issues, and to create strategies for business improvement based on the maslahah hajiyyah principle. The study uses a qualitative method, employing SWOT analysis, with data gathered from semi-structured interviews with the business owner and customers, as well as direct observations conducted over two weeks. The results show that the strengths of Rumah Makan Rani lie in its authentic local flavors, halal-certified ingredients, and excellent customer service. However, weaknesses were found in its limited menu variety and low use of digital marketing, which has led to fewer repeat customers compared to competitors offering more diverse menus and better online presence. The research identifies opportunities for business expansion, such as the growing public interest in local cuisine and the increasing popularity of social media platforms, while challenges include fierce competition and rising costs of raw materials. Based on these insights, the study suggests that the business should diversify its menu and leverage digital platforms like Instagram and Facebook to share updates and engage customers. This research aims to offer practical recommendations for small culinary businesses to create sustainable models that bring greater social and economic value to the community.